Recent Advances in Asthma Research and Treatments - Chapoval, Svetlana P. (IntechOpen, 2022)
This book provides an insightful and analytical look at several aspects related to asthma. Written by experts in the field, chapters cover such topics as asthma phenotypes and current biological treatments, anaphylactic reactions in radiology procedures, asthma and COVID-19, mobile apps for both patients and providers, the function of non-coding RNAs in asthma mediated by Th2 cells, and the roles of B7 and semaphorin molecules. The book provides readers the information they need to get a clear understanding of asthma, its phenotypes, treatment biologics, COVID-19 effects, digital care frameworks, epigenetics, and costimulators/immune checkpoints.